Molecular Identification of 16S RNA of Pathogenic Bacteria From The Wings of Flesh Flies (Sarcophaga sp.) Inspired by The Hadith of The Prophet SAW, Bukhari’s History About Flies - masri, Mashuri; Hajrah, Hajrah; Asfiana, Asfiana; Rusny, Rusny; Lubis, Syafrina sari (Elkawnie, 2025)
Abstract: Meat flies (Sarcophaga sp.) are one of the vectors of infection. Meat flies often fly by using contact wings with legs so that the fly’s flying area is very wide. This study uses qualitative and exploratory methods aimed at knowing the types of bacteria that can be found on the wings of meat flies (Sarcophaga sp.) through molecular identification. Samples were taken from the body parts of the right and left wings of meat flies which were coded (B1) left wing of fly 1; (A2) right wing of fly 2; (B2) left wing of fly 2; (A3) right wing of fly 3; (B3) left wing of fly 3; (A4) right wing of fly 4; (B4) left wing of fly 4; (A5) right wing of fly 5; (B5) left wing of fly 5. Meat fly wings (Sarcophaga sp.) were inoculated on BHIB day NA medium, and molecular identification day was done using 16S RNA. Based on molecular data, pathogenic bacteria were found in sample A5: Bacillus cereus, B. anthracis, and B. tropicus; and in sample B5, Moellerella wisconsensis was found. This research can provide a biological explanation of the hadith of the Prophet Muhammad (peace be upon him) about flies, indicating the presence of pathogenic bacteria on the wings of flesh flies (Sarcophaga sp.). Abstrak: Lalat daging (Sarcophaga sp.) merupakan salah satu vektor berbagai penyakit infeksi. Lalat daging banyak bergerak dengan menggunakan sayap dibandingkan dengan kaki, sehingga area terbang lalat sangat luas. Penelitian ini menggunakan metode kualitatif dan eksploratif yang bertujuan untuk mengetahui jenis bakteri yang terdapat pada sayap lalat daging (Sarcophaga sp.) melalui identifikasi molekuler. Sampel diambil dari bagian tubuh lalat daging sayap kanan dan kiri yang diberi kode (B1) sayap kiri lalat 1; (A2) sayap kanan lalat 2; (B2) sayap kiri lalat 2; (A3) sayap kanan lalat 3; (B3) sayap kiri lalat 3; (A4) sayap kanan lalat 4; (B4) sayap kiri lalat 4; (A5) sayap kanan lalat 5; (B5) sayap kiri lalat 5. Sayap lalat daging (Sarcophaga sp.) diinokulasi pada medium BHIB dan NA, dan identifikasi molekuler menggunakan 16S RNA.  Berdasarkan data molekuler ditemukan bakteri patogen pada sampel A5, yaitu Bacillus cereus, B. anthracis, dan B. Tropicus; pada sampel B5 ditemukan Moellerella wisconsensis. Hasil penelitian ini dapat membuktikan kebenaran hadits Rasululloh SAW tentang lalat dari perspektif biologis dengan membuktikan adanya bakteri patogen yang ditemukan pada sayap lalat daging (Sarcophaga sp.).